2016
DOI: 10.1002/mc.22483
|View full text |Cite
|
Sign up to set email alerts
|

β-ionone modulates the expression of miRNAs and genes involved in the metastatic phenotype of microdissected persistent preneoplastic lesions in rats submitted to hepatocarcinogenesis

Abstract: MicroRNAs (miRNAs) are post-transcriptional gene expression regulators which expression is frequently altered in hepatocellular carcinoma (HCC). β-ionone (βI) is noted for its ability to inhibit persistent preneoplastic lesions (pPNLs) in liver rats. We evaluated the expression of miRNAs involved in carcinogenesis and possible targets modulated by βI, in pPNLs and surrounding of microdissected tissues. Rats subjected to resistant hepatocyte model were treated during promotion stage with βI (16 mg/100 g body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…A recent on-topic study reported interesting nutrigenomic data regarding the miRNA and histone deacetylase modulation ability of some of these foods and drinks peculiar to these countries with no corresponding examples in the MD. The largely used corn, for example, in the form of corn oil induces a differential profile of the expression of tens of miRNAs related to carcinogenesis in the micro dissected liver of rats [136]. Moreover, the kaempferol, contained in grapes, green tea, and potatoes; the resveratrol of grapes, red wine, blueberries, and peanuts; the sinapinic acid in wine and vinegar; the diallyl disulfide of garlic; and the zerumbone of ginger have recently been considered as "natural HDAC inhibitors" [137] and show an in vitro anti-mitotic effect by regulating miRNAs involved in tumor suppression [138].…”
Section: American Foodsmentioning
confidence: 99%
“…A recent on-topic study reported interesting nutrigenomic data regarding the miRNA and histone deacetylase modulation ability of some of these foods and drinks peculiar to these countries with no corresponding examples in the MD. The largely used corn, for example, in the form of corn oil induces a differential profile of the expression of tens of miRNAs related to carcinogenesis in the micro dissected liver of rats [136]. Moreover, the kaempferol, contained in grapes, green tea, and potatoes; the resveratrol of grapes, red wine, blueberries, and peanuts; the sinapinic acid in wine and vinegar; the diallyl disulfide of garlic; and the zerumbone of ginger have recently been considered as "natural HDAC inhibitors" [137] and show an in vitro anti-mitotic effect by regulating miRNAs involved in tumor suppression [138].…”
Section: American Foodsmentioning
confidence: 99%
“…In order to confirm the exogenous miR-708 is functional in cells, c-kit(+) CSCs/CPCs were transfected with miR-708 mimics. After 24 h, RNA was isolated and gene expression was analyzed for predicted target genes including PPARα (peroxisome proliferator-activated receptor alpha) which has not been reported yet, and N-Ras (N-Rasproto-oncogene) and Mtss1 (metastasissuppressor 1) which have been reported to be two target genes of miR-708 in rat [ 20 , 21 ]. As shown in Figure 4 A,B, rat PPARα mRNA has one binding site to miR-708, which is highly conserved between species.…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to previous studies, there is evidence for miR-708-5p to function as an oncogenic miRNA in HCC. Researchers showed that miR-708-5p was overexpressed in persistent preneoplastic liver lesions (pPNLs) compared to surrounding normal liver tissue in rats [ 149 ]. Treatment with β-Ionone, a suppressor of pPNL growth, decreased miR-708-5p levels [ 149 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers showed that miR-708-5p was overexpressed in persistent preneoplastic liver lesions (pPNLs) compared to surrounding normal liver tissue in rats [ 149 ]. Treatment with β-Ionone, a suppressor of pPNL growth, decreased miR-708-5p levels [ 149 ]. miR-708-5p expression also negatively correlated with two tumor suppressors, metalloproteinase inhibitor 3 (Timp3) and metastasis suppressor protein 1 (Mtss1) levels, leading the authors to conclude miR-708-5p acts as a transformative promoter in liver cells [ 149 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation